The effect of Poly(Ethylene oxide) cross-linking structure on the mechanical properties and CO2 separation performance of an ion gel membrane. (10th October 2019) - Kusuma, Victor A.; Chen, Christina; Baker, James S.; Macala, Megan K.; Hopkinson, David
Abstract: Ionic liquid gels of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide plasticizing a cross-linked poly(ethylene oxide) are high performance CO2 separation membranes. Here, the effect of polymer cross-link density on the ionic liquid stability, on the mechanical properties of the resulting films, and on the gas separation properties were studied. Cross-link density was modified by changing the chain length of ethoxylated diacrylate and triacrylate monomers, and by incorporating small amounts of short, multifunctional acrylate monomers. Without the ionic liquid acting as permanent plasticizer, higher cross-link density is associated with higher yield strength but lower strain at break, as expected. In a plasticized network, however, the loss in flexibility is not accompanied by higher yield strength, leaving ion gels made from highly cross-linked network more fragile than those having longer, more flexible chains. Lowering cross-link density also allowed more ionic liquids to be incorporated as a phase stable gel and led to better CO2 separation performance. Graphical abstract: Image 1 Highlights: Fabricated cross-linked poly(ethylene oxide) photopolymerized with ionic liquid. Cross-link density varied by selection of polymer precursor. Tensile and gas permeability tests performed on ion gel films. Lower cross-link density can give better tensile properties and higher permeability.